Occlusion preconditioned mice are resilient to hypobaric hypoxia-induced myocarditis and arrhythmias due to enhanced immunomodulation, metabolic homeostasis, and antioxidants defense - Adzika, Gabriel Komla; Mprah, Richard; Rizvi, Ruqayya; Adekunle, Adebayo Oluwafemi; Ndzie Noah, Marie Louise; Wowui, Prosperl Ivette; Adzraku, Seyram Yao; Adu-Amankwaah, Joseph; Wang, Fengli; Lin, Yuwen; Fu, Lu; Liu, Xiaomei; et al. (Frontiers in Immunology, 2023)
ABSTRACT Sea-level residents experience altitude sickness when they hike or visit altitudes above ~2,500 m due to the hypobaric hypoxia (HH) conditions at such places. HH has been shown to drive cardiac inflammation in both ventricles by inducing maladaptive metabolic reprogramming of macrophages, which evokes aggravated proinflammatory responses, promoting myocarditis, fibrotic remodeling, arrhythmias, heart failure, and sudden deaths. Currently, the use of salidroside or altitude preconditioning (AP) before visiting high altitudes has been extensively shown to exert cardioprotective effects. Even so, both therapeutic interventions have geographical limitations and/or are inaccessible/unavailable to the majority of the population as drawbacks. Meanwhile, occlusion preconditioning (OP) has been extensively demonstrated to prevent hypoxia-induced cardiomyocyte damage by triggering endogenous cardioprotective cascades to mitigate myocardial damage. Herein, with the notion that OP can be conveniently applied anywhere, we sought to explore it as an alternative therapeutic intervention for preventing HH-induced myocarditis and cardiac arrhythmia. OP intervention (applying to the hindlimb a 200 mmHg for 5 min/ 5 min reperfusion at 0 mmHg, 6 cycles daily for 7 days) was performed, and its impact on cardiac electric activity, hypertrophy and injury, immunoregulation, oxidative stress responses, and behavioral outcomes were assessed before and after exposure to HH. By comparing the outcomes of OP to AP interventions, we observed that similar to the latter, OP preserves cardiac electric activity, mitigates maladaptive myocardial remodeling, induces adaptive immunomodulation and metabolic homeostasis in the heart, enhances antioxidant defenses, and confers resistance against HH-induce anxiety-related behavior. Overall, these findings demonstrate that OP is a potent alternative therapeutic intervention for preventing hypoxia-induced myocarditis, arrhythmias, and cardiometabolic disorders and could potentially ameliorate the progression of other oxidative stress-related diseases.